Strain Elastography of Breast and Prostata Cancer: Similarities and Differences - Daniaux, M.; Auer, T.; De Zordo, T.; Junker, D.; Santner, W.; Hubalek, M.; Jaschke, W.; Aigner, F. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Typically both breast and prostate cancer present as tissue with decreased elasticity. Palpation is the oldest technique of tumor detection in both organs and is based on this principle. Thus an operator can grade a palpable mass as suspicious for cancer. Strain elastography as modern ultrasound technique allows the visualization of tissue elasticity in a color coded elastogram and can be understood as technical finger. The following article shows similarities and differences of ultrasound strain elastography in the diagnosis of breast and prostate cancer.Key Points:• In prostata cancer elastography, in breast cancer B-mode is the primary sonographic search modality. • The diagnostic value of the search modalities change with increasing age.• A cut-off value for a strain ratio is hard to obtain in the elastography of the prostata, because there is no stabile reference tissue in the prostata. Citation Format:• Daniaux M, Auer T, De Zordo T et al. Strain Elastography of Breast and Prostata Cancer: Similarities and Differences. Fortschr Röntgenstr 2016; 188: 1 – 6
Keywords: breast; prostate; ultrasound